Cardiovascular manifestations in COVID-19 patients - Jyotsna Maddury; Mani Krishna; Achukatla Kumar (Apollo Medicine, 2022)
Most important medical challenge during the past 2 years is the COVID-19 pandemic due to SARS-CoV-2 virus. COVID-19 morbidity is increased in the presence of CAD risk factors. Effect of CAD risk factors and COVID-19 infection are bidirectional. Preexisting conditions, such as cardiovascular disease (CVD), hypertension, diabetes, and obesity, increase the severity as well as mortality rate of COVID. COVID-19 disease induces multiple cardiovascular manifestations, such as myocarditis, acute myocardial injury, acute myocardial infarction (MI), stress-induced cardiomyopathy, cardiogenic shock, arrhythmias, and, subsequently, heart failure (HF) and cardiac arrest. Increase of troponin suggests a hyperinflammatory state or may be due to acute myocarditis. Elevated troponin without other laboratory markers elevation suggests aggressive COVID-19 disease than myocardial injury. Stress or takotsubo cardiomyopathy occurred primarily in women with COVID-19 and these women have more severe HF. The patients with COVID-19 positive more frequently have multivessel thrombosis, stent thrombosis, and a higher thrombus when compared to COVID-19-negative STEMIs. Because of higher thrombus burden more usage of glycoprotein IIb/IIIa (GP IIb/IIIa) inhibitors and thrombus aspiration and higher heparin doses to achieve therapeutic activated clotting times were also noted. Patients with pulmonary embolism had significantly higher hs-cTnT and NT pro-BNP levels than those without pulmonary embolism. In COVID-19, arrhythmias noticed are atrioventricular/ventricular block, sinus tachycardia, sinus bradycardia, atrial arrhythmias, and ventricular arrhythmias. Consideration for potential drug interactions should be taken when treating CVD patients with COVID-19.